Discovery of a novel class of heteroaryl-pyrrolidinones as positive allosteric modulators of the muscarinic acetylcholine receptor M1. (1st September 2021) - Spearing, Paul K.; Cho, Hyekyung P.; Luscombe, Vincent B.; Blobaum, Anna L.; Boutaud, Olivier; Engers, Darren W.; Rodriguez, Alice L.; Niswender, Colleen M.; Jeffrey Conn, P.; Lindsley, Craig W.; Bender, Aaron M.
Graphical abstract: Abstract: This Letter describes the synthesis and optimization of a series of heteroaryl-pyrrolidinone positive allosteric modulators (PAMs) of the muscarinic acetylcholine receptor M1 (mAChR M1 ). Through the continued optimization of M1 PAM tool compound VU0453595, with a focus on replacement of the 6, 7-dihydro-5 H -pyrrolo[3, 4- b ]pyridin-5-one with a wide variety of alternative 4, 5-dihydropyrrolo-fused heteroaromatics, the generation of M1 PAMs with structurally novel chemotypes is disclosed. Two compounds from these subseries, 8b (VU6005610) and 20a (VU6005852), show robust selectivity for the M1 mAChR, and no M1 agonism. Both compounds have favorable preliminary PK profiles in vitro; 8b additionally demonstrates high brain exposure in a rodent IV cassette model.